Teaching the Communication Course: Intercultural Communication - Nathan G. Webb; Mary Stairs Vaughn (Central States Communication Association, 2019)
Intercultural Communication is a course that can help individuals gain the knowledge and tools to be an effective communicator in a globalized world. This article seeks to answer the question about what students enrolled in an Intercultural Communication course should learn. Specifically, the Intercultural Communication course is examined by examining its foundations, content areas, applied assignments, and issues to consider.